2019
DOI: 10.1136/postgradmedj-2019-136513
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in antihypertensive drug use and blood pressure control

Abstract: BackgroundHypertension is the most important modifiable cardiovascular risk factor. Epidemiological studies have shown the benefits of lowering blood pressure (BP), but BP control is a major challenge. Furthermore, there are significant sex differences in antihypertensive drug use and BP control. This study examined sex differences in antihypertensive drug use and BP control, with the aim of reducing the complications of hypertension and improving quality of life.MethodsThe study was performed in our outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Wang et al reported that in patients aged 18-44 years, angiotensin-converting enzyme inhibitors showed the best control rate in males, while calcium channel blockers were least effective. Inpatients aged 45-64 years, diuretics showed the best control rate in females, while calcium channel blockers were least effective [24]. Klungel et al reported that the different patterns of antihypertensive drug use among hypertensive men and women seem irrational and that among those on monotherapy for hypertension, women were less likely than men to be using a β-blocker, a calcium antagonist, or an angiotensinconverting enzyme inhibitor than a diuretic [25].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al reported that in patients aged 18-44 years, angiotensin-converting enzyme inhibitors showed the best control rate in males, while calcium channel blockers were least effective. Inpatients aged 45-64 years, diuretics showed the best control rate in females, while calcium channel blockers were least effective [24]. Klungel et al reported that the different patterns of antihypertensive drug use among hypertensive men and women seem irrational and that among those on monotherapy for hypertension, women were less likely than men to be using a β-blocker, a calcium antagonist, or an angiotensinconverting enzyme inhibitor than a diuretic [25].…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the characteristics of the drug and the individual ( Table 2 ), which are extensively reviewed [ 38 , 47 , 48 ], the pharmacological response depends on other numerous factors and their interactions [ 49 ], which are summarized in Figure 1 . Sex and gender differences involve drug consumption [ 6 , 50 , 51 , 52 , 53 ] and adherence to therapy, which usually tends to be larger in men and women, respectively, with some exceptions [ 54 , 55 ].…”
Section: Factors That Can Affect the Pharmacological Responsementioning
confidence: 99%
“…observed (1,(5)(6)(7)(8)(9)(10)(11)(12)(13). For example, sex differences in the Renin Angiotensin Aldosterone System, speci cally in androgen and estrogen receptor expression, have been observed in animals and humans (6,(8)(9)(10)(11)13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sex differences in the Renin Angiotensin Aldosterone System, speci cally in androgen and estrogen receptor expression, have been observed in animals and humans (6,(8)(9)(10)(11)13). Several studies have identi ed sex-speci c single nucleotide polymorphisms associated with HT and disparities between women and men in pharmacogenetic drug responses to available therapies (7,(14)(15)(16). Additionally, women generally have lower BP than men prior to the onset of menopause (16).…”
Section: Introductionmentioning
confidence: 99%